(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes a system that analyses the requirements of people with autism spectrum disorder and to alter the caretaker to acknowledge the present feeling in them to ease sure activity problems. This may be achieved through sensible devices. The smartwatch system monitors the feeling through the galvanic skin response and graphical record, that measures the electrical physical phenomenon of the skin and electrical signals from the scalp of the brain. The signals area unit digitized. Then acceptable emotions area unit classified through the Support Vector Machine algorithmic program. The intensity and therefore the form of feeling area unit flashed on the caretaker’s communication device